2018
DOI: 10.1105/tpc.18.00276
|View full text |Cite
|
Sign up to set email alerts
|

PUX10 Is a Lipid Droplet-Localized Scaffold Protein That Interacts with CELL DIVISION CYCLE48 and Is Involved in the Degradation of Lipid Droplet Proteins

Abstract: The number of known proteins associated with plant lipid droplets (LDs) is small compared with other organelles. Many aspects of LD biosynthesis and degradation are unknown, and identifying and characterizing candidate LD proteins could help elucidate these processes. Here, we analyzed the proteome of LD-enriched fractions isolated from tobacco (Nicotiana tabacum) pollen tubes. Proteins that were highly enriched in comparison with the total or cytosolic fraction were further tested for LD localization via tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(123 citation statements)
references
References 109 publications
(155 reference statements)
4
114
0
Order By: Relevance
“…These distinct motifs designate oleosins toward different degradation pathways according to the ubiquitination type. Deruyffelaere et al further confirmed that PUX10 localized to OBs interacts directly with ubiquitinated oleosins and mediates dislocation of oleosins by the AAA ATPase CDC48A (Deruyffelaere et al, 2018;Kretzschmar et al, 2018).…”
Section: Interactions Between Ob-associated Proteins and Other Proteinsmentioning
confidence: 87%
See 2 more Smart Citations
“…These distinct motifs designate oleosins toward different degradation pathways according to the ubiquitination type. Deruyffelaere et al further confirmed that PUX10 localized to OBs interacts directly with ubiquitinated oleosins and mediates dislocation of oleosins by the AAA ATPase CDC48A (Deruyffelaere et al, 2018;Kretzschmar et al, 2018).…”
Section: Interactions Between Ob-associated Proteins and Other Proteinsmentioning
confidence: 87%
“…PUX10 localizes to OBs and binds to the ubiquitinated oleosins via its hydrophobic domain and interacts with ubiquitin and CDC48A via its UBA and UBX domains, respectively. As an adaptor, PUX10 recruits CDC48A to ubiquitinated oleosins, leading to dislocation of oleosins from OBs via the segregase activity of CDC48A (Deruyffelaere et al, 2018;Kretzschmar et al, 2018).…”
Section: Oleosins Play An Important Role In Ob Formation and Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…and K63-linked diubiquitin K63Ub2) allowing addressing this protein to the 26S proteasome in the cytosol for its degradation [127]. It has been recently shown, by two independent teams, in the pollen tube of Nicotiana tabacum and in germinating seedlings of Arabidopsis thaliana, that the protein PUX10 (Plant UBX Domain-containing Protein 10), located on the surface of LDs, participated in the recognition of polyubiquitinated K48 motifs with its UBA domain [127,128]. PUX10, via its UBX domain, recruits the AAA-type ATPase Cell Division Cycle 48 protein (CDC48), a protein involved in the ERAD (Endoplasmic-reticulum-associated protein degradation) pathway.…”
Section: A Proteome Indicating a Proximity With The Endomembrane Systemmentioning
confidence: 99%
“…Oleosin family protein (Deruyffelaere et al, 2015;Kretzschmar et al, 2018) AT3G01670 Unknown protein AT3G02130 RPK2/TOAD2/CLI1 AT3G03050 CSLD3/KJK/ATCSLD3 (Gu et al, 2016) AT3G03310 ATLCAT3 AT3G04120 GAPC/GAPC-1 (Peralta et al, 2016) AT3G04840 Ribosomal protein S3Ae (Kim et al, 2013;Svozil et al, 2014;Walton et al, 2016) Heat shock protein 70 (Hsp 70) family protein (Walton et al, 2016;Romero-Barrios et al, 2020) AT3G09740 SYP71 (Walton et al, 2016;Romero-Barrios et al, 2020) AT3G09840 CDC48,/CDC48A (Kim et al, 2013;Walton et al, 2016…”
Section: At2g45820mentioning
confidence: 99%